Politická komunikace české stavovské opozice roku 1547 (Regionální aspekt a role „Přátelského snešení“ ve stavovském odboji) - Petr Vorel (Theatrum Historiae)
The author considers the possibilities of the communication within the noble class of the Bohemian society at the time of the revolt of the Estates in 1547. He defines three basic communication layers: 1) informal meetings in the residences of eminent magnates (replacing the banned regional assemblies) passed off as the participation in the usual social events of that time; 2) communication by means of the network of couriers delivering the declarations of the Estates, in a written or printed form, to the Bohemian regions; 3) talks of an assembly character, in which resolutions of wider (countrywide) efficiency were adopted. In this context, the author gives an idea of the meaning of the text called “Friendly Resolution” which he primarily regards as the opposition programme of the Estates approved by the assembly talks, unauthorized by the king, in March 1547. He also recapitulates the development of the interpretation of the term “Friendly Resolution” in earlier interpretations.